The social media usage and their effect on Tourism marketing behavior A Study among University International Students in Indonesia - Bejaoui, Asma; Rahayu, Agus; Dirgantari, Puspo Dewi (Ekonomis: Journal of Economics and Business, 2024)
This study investigates the impact of social media on tourism marketing behavior among international students in Indonesia. Employing a descriptive research method utilizing a qualitative approach, in some groups it was conducted with international students to explore their travel experiences and the influence of social media on their destination choices. The findings reveal that social media plays a significant role in shaping students' travel decisions, with a particular emphasis on the importance of visual platforms like Instagram and YouTube and their specific interests in how and where to visit with the help of these platforms. This research contributes to the existing literature on the role of social media in tourism marketing and provides insights into the preferences and behaviors of international students, a key demographic in the tourism industry. The discussion covers the range of interests that students have in artificial, cultural, and natural tourism as well as more niche types including MICE, health, and information tourism. Notably, participants stressed the need for thorough travel information, especially about lodging, meals, transportation, and guided tours information that is mostly found online. The study emphasizes how social media use and the diverse range of tourist experiences that foreign students in Indonesia are looking for are intricately related. Overall, this investigation clarifies the mutually beneficial relationship between social media dynamics and traveller behaviours, revealing information that is essential for academics and industry participants to comprehend in order to fully utilize digital platforms in modern tourism.